Genetic and Environmental Factors Contributing to Parkinson's Disease: A Case-Control Study in the Cypriot Population - Georgiou, Andrea; Demetriou, Christiana A.; Christou, Yiolanda P.; Heraclides, Alexandros; Leonidou, Eleni; Loukaides, Panayiotis; Yiasoumi, Elena; Pantziaris, Marios; Kleopa, Kleopas A.; Papacostas, Savvas S.; Loizidou, Maria A.; Hadjisavvas, Andreas; et al. (Frontiers in Neurology, 2019)
Introduction: Parkinson's disease (PD) is a neurodegenerative disorder affecting a substantial proportion of the elderly Cypriot population. The objective of this study was to evaluate PD risk variants that have been identified previously in Genome Wide Association Studies (GWAS) and to find environmental factors that are predictors for PD onset in the Cypriot population. Methods: A case-control study was conducted with a total of 235 PD patients and 464 healthy controls of Greek-Cypriot ethnicity. Demographic and lifestyle characteristics, exposure to PD risk factors and clinical data were collected. Moreover, 13 previously GWAS-identified PD risk variants were genotyped. Univariate and multivariate regression analyses examined the association between a number of environmental and genetic factors and PD. Results: Multivariable regression analysis revealed that exposure to both pesticides and other toxic substances (P = 0.03), severe head injury accompanied with fainting (P = 0.001), nuts consumption (P = 0.004), red meat consumption (P = 0.02), and soft drinks consumption (P = 0.008) were increasing the risk for PD, whereas cumulative smoking (P = 0.02), and fish consumption (P = 0.02) were decreasing the risk for PD. Five out of the 13 tested SNPs (rs12185268, rs6599389, rs356220, rs13312, and rs17649553) were confirmed to be nominally significantly associated (P < 0.05) with PD risk in the Cypriot population. Conclusions: Collectively, this case-control study has shed some light on the nature of PD epidemiology in Cyprus, by demonstrating a number of genetic and environmental determinants of PD in the Cypriot population.